Peranan Industri Kecil Terhadap Penyerapan Tenaga Kerja di Kota Kendari - Kalean, Farhan Aldilan; Rostin, Rostin; Apoda, Apoda (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
The purpose of this study is to find out how big the role of small industry inKendari city is from 2010 to 2019. The research method used is to use return data in the period 2010-2019,with data on the number of workers in the city of Kendari and the number ofworkers who work in small industries in the city of Kendari in 2010-2019. The data that has been obtained is ???? =????????/????????× 100 then described using a formula to find out how big the role of small industry is to the absorption of labor in the city of Kendari. The results showed that; The role of small industry in the city of Kendari is still relatively small calculated from 2010-2019 with an average workforceabsorbed of 11 percent. The highest absorbed workforce was in 2010 and 2013 which both absorbed 13.96 percent of the workforce